SUMO and SUMOylation Pathway at the Forefront of Host Immune Response - K., Sajeev T.; Joshi, Garima; Arya, Pooja; Mahajan, Vibhuti; Chaturvedi, Akanksha; Mishra, Ram Kumar (Frontiers in Cell and Developmental Biology, 2021)
Pathogens pose a continuous challenge for the survival of the host species. In response to the pathogens, the host immune system mounts orchestrated defense responses initiating various mechanisms both at the cellular and molecular levels, including multiple post-translational modifications (PTMs) leading to the initiation of signaling pathways. The network of such pathways results in the recruitment of various innate immune components and cells at the site of infection and activation of the adaptive immune cells, which work in synergy to combat the pathogens. Ubiquitination is one of the most commonly used PTMs. Host cells utilize ubiquitination for both temporal and spatial regulation of immune response pathways. Over the last decade, ubiquitin family proteins, particularly small ubiquitin-related modifiers (SUMO), have been widely implicated in host immune response. SUMOs are ubiquitin-like (Ubl) proteins transiently conjugated to a wide variety of proteins through SUMOylation. SUMOs primarily exert their effect on target proteins by covalently modifying them. However, SUMO also engages in a non-covalent interaction with the SUMO-interacting motif (SIM) in target proteins. Unlike ubiquitination, SUMOylation alters localization, interactions, functions, or stability of target proteins. This review provides an overview of the interplay of SUMOylation and immune signaling and development pathways in general. Additionally, we discuss in detail the regulation exerted by covalent SUMO modifications of target proteins, and SIM mediated non-covalent interactions with several effector proteins. In addition, we provide a comprehensive review of the literature on the importance of the SUMO pathway in the development and maintenance of a robust immune system network of the host. We also summarize how pathogens modulate the host SUMO cycle to sustain infectability. Studies dealing mainly with SUMO pathway proteins in the immune system are still in infancy. We anticipate that the field will see a thorough and more directed analysis of the SUMO pathway in regulating different cells and pathways of the immune system. Our current understanding of the importance of the SUMO pathway in the immune system necessitates an urgent need to synthesize specific inhibitors, bioactive regulatory molecules, as novel therapeutic targets.